2021
DOI: 10.7759/cureus.17413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcome of Snake Bites Among Children Admitted in the Emergency Pediatric Unit, Federal Medical Centre, Birnin Kebbi, Nigeria

Abstract: Introduction Snakebites are common and constitute an important health problem in many countries of the world, with the greatest burden occurring in rural areas of Asia and Sub-Saharan Africa. They were classified by the World Health Organization as category A of neglected tropical diseases. Most studies on snake envenoming in Nigeria were among adult populations with few among children. This study assessed the prevalence and outcome of snakebite among children in Federal Medical Centre, Birnin Kebbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Studies done in Nepal and Nigeria showed that snakebite in children could have higher mortality, owing to the lower volume of distribution relative to the amount of venom injected [ 68 , 69 ]. Case fatality in our study was low (<2%), which is in line with many findings from studies done in tropical and subtropical countries [ 70 72 ], and none of those who died were aged less than 18 years. We found a slightly high number of female snakebite victims, which may be due to a higher exposure during daily activities such as fetching water, firewood and farming that usually happen early in the morning or late in the evening.…”
Section: Discussionsupporting
confidence: 92%
“…Studies done in Nepal and Nigeria showed that snakebite in children could have higher mortality, owing to the lower volume of distribution relative to the amount of venom injected [ 68 , 69 ]. Case fatality in our study was low (<2%), which is in line with many findings from studies done in tropical and subtropical countries [ 70 72 ], and none of those who died were aged less than 18 years. We found a slightly high number of female snakebite victims, which may be due to a higher exposure during daily activities such as fetching water, firewood and farming that usually happen early in the morning or late in the evening.…”
Section: Discussionsupporting
confidence: 92%
“…29 Moreover, there was a low prevalence (0.0037 or 3.7/1000, 19 snakebite cases out of 5195 admissions) of snakebites among children admitted in Nigeria. 30 However, the case fatality rate was 5.6% among these children. 30 Interestingly, in Kenya, 382 community respondents reported that 9.1% of bitten community members and 14.6% of bitten family members died from snakebites.…”
Section: Discussionmentioning
confidence: 83%
“… 30 However, the case fatality rate was 5.6% among these children. 30 Interestingly, in Kenya, 382 community respondents reported that 9.1% of bitten community members and 14.6% of bitten family members died from snakebites. 31 Thus, it seems that snakebite is a neglected health problem in Sudan and more effort is required to address this problem.…”
Section: Discussionmentioning
confidence: 99%